Epidemiological study of porcine sapelovirus infection in pigs at Bareilly area of Uttar Pradesh, India. Issue 8 (16th November 2020) - Kumari, Swati; Singh, Rahul; Saikumar, G.
ABSTRACT: An epidemiological study was conducted along with real-time polymerase chain reaction (PCR) detection of porcine sapelovirus (PSV) infection in pigs from Bareilly district of Uttar Pradesh (UP), India. Different epidemiological parameters such as age, sex, clinical sign and seasonal changes in a year were recorded. A total of 90 faecal/intestinal contents samples were screened for PSV infection using real-timebased on Taqman probe assay, targeted 5ʹUTR regions of PSV. Out of 90 collected faecal/intestinal contents, 23.3% (21/90) of the samples were positive for PSV. The prevalence of PSV was recorded in necropsied animals from postmortem facility, Indian Veterinary Research Institute (IVRI) (16%), swine production farm, IVRI (44.4%) and slaughtered animals (21.7%) from Bareilly regions. Age-wise highest prevalence of PSV was found in 29–56 days (33.3%) age group followed by 57–140 days age group (25%) and 0–28 days (13.9%) age group. Sex-wise prevalence was recorded higher in female (25%) than male (22.85%). Seasonally, the prevalence of PSV was highest ( p < 0.01) in winter (30%) followed by monsoon (23.3%) and summer (11.1%). The observations of the present study would provide a basis for a further effective explorative surveillance and epidemiological studies to know the real impact of PSV infection in pigs population of India.